Tác động của năng lực quá trình tri thức tới năng lực đổi mới: Nghiên cứu trong các trường đại học tại Việt Nam - Nguyễn Thị Hồng, Anh; Nguyễn Duy, Thành; Đặng Thị Việt, Đức (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
This study used a second-order construct to examine the relationship between knowledge process capability and innovation capability. Specifically, knowledge process capability is a second-order construct comprising three components: knowledge creation, knowledge dissemination, and knowledge application. Innovation is also a second-order construct, consisting of two components: innovation speed and innovation quality. The estimation results with a second-order construct based on a sample of 297 staff and lecturers from 35 public and private universities across 10 provinces and cities in Vietnam, using the Partial Least Squares Structural Equation Modeling (PLS-SEM), indicate that knowledge process capability has a positive impact on innovation capability. This result will help managers in Vietnamese universities clearly realize the importance of applying knowledge process capability to improve innovation activities, thereby improving organisational performance.